Quantifying the Impact of Public Perceptions on Vaccine Acceptance Using Behavioral Economics - Hursh, Steven R.; Strickland, Justin C.; Schwartz, Lindsay P.; Reed, Derek D. (Frontiers in Public Health, 2020)
This study was conducted to evaluate the impact of public perceptions of vaccine efficacy on intent to seek COVID-19 vaccination using hypothetical vaccine acceptance scenarios. The behavioral economic methodology could be used to inform public health vaccination campaigns designed to influence public perceptions and improve public acceptance of the vaccine. In June 2020, 534 respondents completed online validated behavioral economic procedures adapted to evaluate COVID-19 vaccine demand in relation to a hypothetical development process and efficacy. An exponential demand function was used to describe the proportion of participants accepting the vaccine at each efficacy. Linear mixed effect models evaluated development process and individual characteristic effects on minimum required vaccine efficacy required for vaccine acceptance. The rapid development process scenario increased the rate of decline in acceptance with reductions in efficacy. At 50% efficacy, 68.8% of respondents would seek the standard vaccine and 58.8% would seek the rapid developed vaccine. Rapid vaccine development increased the minimum required efficacy for vaccine acceptance by over 9 percentage points, γ=9.36, p<.001. Past-3-year flu vaccination, γ=-23.00, p<.001, and male respondents, γ=-4.98, p=.037, accepted lower efficacy. Respondents reporting greater conspiracy beliefs, γ=0.39, p<.001, and political conservatism, γ=0.32, p<.001, required higher efficacy. Male, γ=-4.43, p=.013, and more conservative, γ=-0.09, p=.039, respondents showed smaller changes in minimum required efficacy by development process. Information on the vaccine development process, vaccine efficacy, and individual differences impact the proportion of respondents reporting COVID-19 vaccination intentions. Behavioral economics provides an empirical method to estimate vaccine demand to target subpopulations resistant to vaccination.